ANALISIS HAK ATAS MEREK SEBAGAI AGUNAN DALAM PEMBERIAN KREDIT BANK - Raymond Kusuma; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2020)
The use of intellectual property as collateral in providing credit in Indonesia began, where Article 16 of the Creative Economy Law states that the Government facilitates intellectual property financing schemes. The Right to Trademark is part of intellectual property rights, however the recommendation of the Right to Mark in the MIG Law as an object and guarantee is not explicitly written down. Therefore, it must be examined regarding the existence of the Right to Mark as an Object and can be used as a guarantee. Then, if the Right to a Mark is used as an object of guarantee, then the regulation regarding the existing legal structure in which a brand that has unpredictable characteristics will have a fast and easy stability in executing the mark. Referring to this problem, the author uses the normative juridical method. The results of the analysis show that the Right to Mark is an object, that is, with the type of movable and intangible object due to the nature of the material, the Right to Mark can be guaranteed and become a general guarantee in Article 1131 of the Civil Code. Trademark rights, if used as collateral, still give the impression and are not friendly to the bank. Currently, the Appraisal Agency can make an assessment of the economic value of the Right to Mark, but only for transactional purposes not for collateral or auction.